Mosquito-borne Diseases - Tolle, Michael A. (Current problems in pediatric and adolescent health care, 2009)
Despite centuries of control efforts, mosquito-borne diseases are flourishing worldwide. With a disproportionate effect on children and adolescents, these conditions are responsible for substantial global morbidity and mortality. Malaria kills more than 1 million children annually, chiefly in sub-Saharan Africa. Dengue virus has expanded its range over the past several decades, following its principal vector, Aedes aegypti, back into regions from which it was eliminated in the mid-20th century and causing widespread epidemics of hemorrhagic fever. West Nile virus has become endemic throughout the Americas in the past 10 years, while chikungunya virus has emerged in the Indian Ocean basin and mainland Asia to affect millions. Japanese encephalitis virus, too, has expanded its range in the Indian subcontinent and Australasia, mainly affecting young children. Filariasis, on the other hand, is on the retreat, the subject of a global eradication campaign. Efforts to limit the effect of mosquito-borne diseases in endemic areas face the twin challenges of controlling mosquito populations and delivering effective public health interventions. Travelers to areas endemic for mosquito-borne diseases require special advice on mosquito avoidance, immunizations, and malaria prophylaxis.